Variables in Terms of Location of Colonic Carcinoma - SHAHID MAHMOOD, SOSAN SHAHID, HAMAD RANA (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Colorectal carcinoma is the third commonest malignancy all over the world. Prognosis is excellent if diagnosed at stage I or II and treated properly. Objectives: To compare the duration of onset of symptoms and time of first presentation in a tertiary care center with the site of tumor. Material & Methods: It is a cross sectional retrospective study. Patients with histological proof of carcinoma were included in the study. Data over the period of two year was collected and analyzed. Results: This study included one hundred patients. Mean age was 49.56 years and 56 % of the patients were males. 40 % of the patients presented between the ages of 40 to 60 years. Mean time of start of symptoms and the time of presentation in the hospital was 6.5 months. It was noted that rectal carcinoma presented earlier with a mean duration of 5 months, as compared to colonic carcinoma where mean time of presentation was 8 months. Among colonic group, right sided masses presented late as compared to left colonic tumors. Mean time was 9.5 month as compare to left side where mean time was 6.5 months. Conclusions: Rectal tumors present in the hospital much earlier as compare to colonic masses. Similarly in colon, left sided tumors present early as compare to ceacal or ascending colon, who present with more advance stage resulting in poor prognosis.